Clogging risk of microplastics particles in porous media during artificial recharge: a laboratory experiment - Wang, Huan; Zhang, Junjie; Chen, Yudao; Xia, Yuan; Jian, Peng; Liang, Haozhi (Frontiers in Marine Science, 2024)
Management aquifer recharge (MAR) technology is widely applied to solve seawater intrusion caused by groundwater overexploitation in coastal areas. However, MAR creates an important pathway for microplastics (particle size< 5 mm) to enter groundwater. To explore the clogging potential of microplastics in aquifer media, a series of laboratory-scale column experiments were conducted in this study. The hydraulic conductivity of porous media and deposition amount of microplastics were investigated under different experimental conditions. In our study, most of the microplastics were intercepted in the sand column’s surface layer. The difference of particle size in porous media greatly influence the clogging development. The hydraulic conductivity of the aquifer media decreased as the microplastic particle size decreased. When the particle size of microplastic was larger than 300 mm, most of the microplastics deposits on the surface of the porous media, forming a “microplastic accumulation layer”. Microplastics are affected by particle size, flow shear stress and preferential flow during migration. The migration ability of microplastics increased significantly with the increase of hydraulic head difference and decreased with the increase of sand column depth. The bacteria microorganisms are projected to be a new biological control strategy in conjunction with MAR. The study of clogging risk of microplastics particles in porous media during artificial recharge provides novel and unique insights for the management and control of microplastic pollution in groundwater systems.